2023
DOI: 10.3390/polym15020396
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Edible Films and Coatings with Added Bioactive Compounds: Antibacterial and Antioxidant Properties and Their Application to Food Products: A Review

Abstract: Chitosan is the deacetylated form of chitin regarded as one of the most abundant polymers and due to its properties, both chitosan alone or in combination with bioactive substances for the production of biodegradable films and coatings is gaining attention in terms of applications in the food industry. To enhance the antimicrobial and antioxidant properties of chitosan, a vast variety of plant extracts have been incorporated to meet consumer demands for more environmentally friendly and synthetic preservative-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 161 publications
1
21
0
Order By: Relevance
“…The results showed that none of the microorganisms mentioned above were detected in CS, CP, and CB after storage for 8 weeks, indicating that the β-carotene emulsions were not threatened by microbes during low-temperature storage without any prior sterilization process. This phenomenon may be related to the strong antibacterial properties of chitosan and seaweed polyphenols, which inhibited the growth of microorganisms during the storage of the emulsions. , Overall, the results presented in Table provide a preliminary positive evaluation of the microbial safety of the use of PEs for the encapsulation of β-carotene. Seaweed polyphenols have been previously reported to contribute to extending the shelf life after adding a variety of other food products, including mayonnaise, fish, and chicken. Moreover, the results of the current research demonstrated the bacteriostatic ability of CP and CB, which could contribute to their industrial applications without adding additional antibacterial agents.…”
Section: Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results showed that none of the microorganisms mentioned above were detected in CS, CP, and CB after storage for 8 weeks, indicating that the β-carotene emulsions were not threatened by microbes during low-temperature storage without any prior sterilization process. This phenomenon may be related to the strong antibacterial properties of chitosan and seaweed polyphenols, which inhibited the growth of microorganisms during the storage of the emulsions. , Overall, the results presented in Table provide a preliminary positive evaluation of the microbial safety of the use of PEs for the encapsulation of β-carotene. Seaweed polyphenols have been previously reported to contribute to extending the shelf life after adding a variety of other food products, including mayonnaise, fish, and chicken. Moreover, the results of the current research demonstrated the bacteriostatic ability of CP and CB, which could contribute to their industrial applications without adding additional antibacterial agents.…”
Section: Results and Discussionmentioning
confidence: 89%
“…This phenomenon may be related to the strong antibacterial properties of chitosan and seaweed polyphenols, which inhibited the growth of microorganisms during the storage of the emulsions. 43,44 Overall, the results presented in Table 1 provide a preliminary positive evaluation of the microbial safety of the use of PEs for the encapsulation of β-carotene. Seaweed polyphenols have been previously reported to contribute to extending the shelf life after adding a variety of other food products, including mayonnaise, fish, and chicken.…”
Section: Measurement Of β-Carotenementioning
confidence: 90%
“…One limitation of pure chitosan films is their poor mechanical strength and water resistance, but these properties can be improved by blending chitosan with other polymers or by modifying its structure to create chitosan derivatives [ 154 , 155 ].…”
Section: The Most Important Chitosan-based Antibacterial Materialsmentioning
confidence: 99%
“…31,36−39 Precedents in the literature have reported the use of chitosan-based materials for such purpose, but, unfortunately, a dramatic decrease of its antibacterial activity has been noticed when shaped as films or sprayed on flat surfaces. 40,41 Additional drawbacks lie on its low chemical stability, with the cross-linking providing a way to enhance the framework stability. 42−44 To address the two long-standing challenges in a single action, we envisioned the cross-linking of chitosan with functionalities able to amplify its antibacterial activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alternatively, ammonium-containing natural polymers derived from nitrogen-rich biomass and more preferably those discarded as biowaste stand as prominent contenders in the realm of antibacterial materials. The gelling capabilities of the polysaccharides, for instance, constitutes an added bonus, owing to their moldable soft structure that could be configured in different forms as end-used devices. The case of chitosan is noteworthy for several reasons: (i) its source, chitin, is the second most abundant polysaccharide on Earth after cellulose, , (ii) it is the sole cationic biopolymer, (iii) it displays a highly reactive amine group for bioconjugation, and its tailor-made handling provides sprayable gels, porous microspheres, and flexible films with controllable thickness. , Precedents in the literature have reported the use of chitosan-based materials for such purpose, but, unfortunately, a dramatic decrease of its antibacterial activity has been noticed when shaped as films or sprayed on flat surfaces. , Additional drawbacks lie on its low chemical stability, with the cross-linking providing a way to enhance the framework stability. To address the two long-standing challenges in a single action, we envisioned the cross-linking of chitosan with functionalities able to amplify its antibacterial activity. We have selected an alkylated quaternary pyridinium derivative, commonly known as viologen. Viologen has been massively used owing to its multifaceted properties (ionic conductivity, photochromic and electrochromic properties, antibacterial properties, and so on).…”
Section: Introductionmentioning
confidence: 99%